Data disaggregation and its discontents: discourses of civil rights, efficiency and ethnic registry. Issue 2 (4th March 2021) - Fu, Shuang; King, Kendall
ABSTRACT: This paper examines recent political debates surrounding data disaggregation in education policy in one US state, and analyses the discourses taken up by supporters and opponents of these policies. Analysis suggests how discourses move across time and space, and focuses on how these discourses are contextualized and entextualized in social media, interaction, and public texts. The paper contributes to our knowledge of a major, but understudied, US education policy movement, and provides insights into how similar discourses are variably taken up by political actors for divergent ends.